Alcoholic extract of propolis for worms control in sheep (Research, Society and Development, 2022)
The objective was to evaluate the antiparasitic effect of different dosages of the alcoholic extract of propolis in the control of verminosis in sheep. Thirty-two Santa Inês sheep were used in a randomized complete block design with four treatments and eight replicates. The treatments were: 10 mL of water; 10 mL of alcohol 70%; 5 mL of propolis alcoholic extract (PAE) 30%; and 10 mL of PAE 30%. The treatments were administered orally, in a single dose. The effects of the treatments were evaluated by counting eggs per gram of faeces (EPG) for days 1; 3; 7 and 21 after administration. Oral administration of 10 mL of water or 10 mL of alcohol 70% had no effect on EPG reduction. The use of 5 mL of PAE 30% reduced EPG on days 3 and 7, reducing its efficacy on day 21, while the use of 10 mL of PAE 30% reduced EPG on all evaluated days. Thus, oral administration, in a single dose, of 10 mL of propolis alcoholic extract 30%, effectively reduced the number of EPG demonstrating antiparasitic effect and can be used in the control of verminoses as an alternative method to chemical products synthetic.